Legal Cartainty in Digital Sharia Business Contracts: Problems of Validity, Sharia Compliance and Dispute Resolution in Makassar - Andi Candrawali Makmur; Widi Rahman; Hannani Hannani; Zainal Said (Pusdikra Publishing, 2026)
This study examines legal certainty in digital sharia business contracts in Makassar, focusing on three dimensions: contract validity, sharia compliance, and dispute resolution mechanisms. Employing empirical legal research with a qualitative approach and purposive sampling of nine key informants comprising judges of the Religious Court of Makassar, sharia compliance officers, Islamic economics academics, OJK Regional 6 officials, DSN-MUI/MUI Sulawesi Selatan members, and Religious Court judiciary the research reveals three principal findings. First, digital sharia contract validity is not fully synchronized between Indonesian positive law (UU ITE) and Islamic economic law (KHES/fiqh muamalah), with critical normative gaps in electronic ijab-qabul standards, digital KYC adequacy, and the formal legal status of DSN-MUI fatwas. Second, sharia compliance operates under a multi-layered normative structure but suffers from serious regulatory lag, disharmony between POJK provisions and DSN-MUI fatwas, and limited digital competency among Sharia Supervisory Boards (DPS). Third, dispute resolution through Religious Courts faces structural barriers including inconsistent judicial interpretation, the absence of a Supreme Court Regulation (Perma) specifically governing digital sharia contract disputes, and inadequate electronic evidence standards. The study concludes that Indonesia requires a comprehensive Digital Sharia Economic Law integrating UU ITE, UU Perbankan Syariah, and fiqh muamalah principles, accompanied by revised KHES provisions on digital akad, a joint OJK-DSN-MUI regulatory committee, and an integrated national shariah digital regulatory portal.